2022
DOI: 10.1101/2022.07.20.500818
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Superficial white matter across the lifespan: volume, thickness, change, and relationship with cortical features

Abstract: Superficial white matter (SWM) represents a significantly understudied part of the human brain, despite comprising a large portion of brain volume and making up a majority of cortical structural connections. Using multiple, high-quality, datasets with large sample sizes (N=2421, age range 5-100) in combination with methodological advances in tractography, we quantified features of SWM volume and thickness across the brain and across the lifespan. We address four questions: (1) How does U-fiber volume change wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 91 publications
1
1
0
Order By: Relevance
“…Here we show that total white matter volume plateaus much before FA, which reverses trends before RD and ICVF. The total white matter volume generally peaks around 18-25 years old, which well-matches the total white matter volume trends [74] which reverse at <25 years old. Yet, cortical surface area peaks before white matter volume.…”
Section: Milestones and Timingssupporting
confidence: 64%
“…Here we show that total white matter volume plateaus much before FA, which reverses trends before RD and ICVF. The total white matter volume generally peaks around 18-25 years old, which well-matches the total white matter volume trends [74] which reverse at <25 years old. Yet, cortical surface area peaks before white matter volume.…”
Section: Milestones and Timingssupporting
confidence: 64%
“…Third, although most seizure-free patients had no abnormal connections with the RZ, this does not imply there were no abnormalities within the RZ. It would be useful to investigate local white matter tracts within RZ ( Chen, Wang, Kopetzky, Butz-Ostendorf, & Kaiser, 2021 ; Schilling et al, 2022 ; Shastin et al, 2022 ). Finally, the postulated epileptogenic zone defined as the RZ may not represent the true epileptogenic foci.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas commonly applied approaches, including tractbased spatial statistics, 16 region-of-interest (ROI) analysis, and tractometry, 17 focus on the core of the major WM bundles, the subcortical WM is gaining attention in studies of both health and disease. 18,19 Histology of ALS has revealed that the degree of pathology, including astrocytosis and astrocyte reactivity, is greater in the subcortical WM than in the GM of the motor cortex. 20 Delamination and unraveling of myelin sheaths in the subcortical WM have also been reported.…”
Section: Introductionmentioning
confidence: 99%